DEVELOPMENT AND VALIDATION OF A HPTLC METHOD FOR SIMULTANEOUS DENSITOMETRIC ANALYSIS OF GLYCYRRHETIC ACID AND SOLASODINE IN HERBAL DRUG FORMULATION - Patel, Kinjal; Bhatt, Chaitanya (International Journal of Current Pharmaceutical Research, 2017)
Objective: To develop and validate a simple, precise, selective, and accurate high-performance thin layer chromatographic method for simultaneous densitometric analysis of glycyrrhetic acid and solasodine in the polyherbal formulation. Methods: The method was developed using HPTLC silica gel GF254precoated aluminium plate as the stationary phase and Chloroform: Methanol (9:1 v/v) as the mobile phase. Quantization of glycyrrhetic acid was achieved by determining the area under the curve at 267 nm using CAMAG TLC Scanner and CATS 3 software. Since the structure of solasodine lacks conjugated double bond, it does not give any fluorescence either in the absorbance mode or reflectance mode hence solasodine was derivatized using 0.5%anisaldehyde sulphuric acids which gave a bluish spot as seen on TLC plate. These spots were scanned at 546 nm wavelength using CAMAG TLC Scanner and CATS 3 software. Results: The retention factor for glycyrrhetic acid and solasodine were found to be 0.52±0.01, 0.40±0.01% w/w respectively. The developed HPTLC method was validated using parameters described in International Conference on Harmonization (ICH) guideline. The proposed method showed good linearity in the range of 400-2000 ng spot-1 for glycyrrhetic acid as well as for solasodine. The content of glycyrrhetic acid and solasodine in marketed polyherbal formulation were found to be 0.67%±0.8 and 0.10±0.35%w/w respectively. Conclusion: The developed method can be used as quality control tool for the routine analysis of glycyrrhetic acid and solasodine in polyherbal formulation.